Thermal stresses in an infinite body with spherical cavity due to an arbitrary heat flux on its internal boundary surface - Kedar, Ganesh D; Pawar, S. P.; Deshmukh, K. C. (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
In this paper we consider an elastic infinite body with a spherical cavity subjected to a arbitrary heat flux on its internal boundary which is assumed to be traction free. The displacement and thermal stresses are obtained and results are compared using constant and time dependent heat flux. Laplace transform technique is used to obtain the temperature distribution. The mathematical model is obtained for copper material. The results are illustrated numerically and graphically.